Simulation Of Gps-Based Train Positioning Information for Lrt Kelana Jaya Line - Raja Ismail, Raja Iman Muhaimin; Nagarajoo, Karthigesu (Progress in Engineering Application and Technology, 2022)
Public Address and Passenger Information System (PA/PIS) is significant in railway industry as it provides multiple information to the passengers including the train’s current and next station location. The information displayed is reliant on the Train’s Positioning Information (TPI) which was gained from multiple sources such as Radio Frequency Identification (RFID) and Global Positioning System (GPS). For Light Railway Transit (LRT) Kelana Jaya Line, signalling and RFID had been used in the past as a source of TPI. However, issues arise from the use of both methods, hence the use of GPS was proposed. The objective of this project is to understand the PA/PIS and GPS concept for TPI, and to analyse the feasibility of the system. The concept of TPI, a brief detail of LRT Kelana Jaya Line, and the working principle of GPS is researched in the literature review section. The process of the GPS-based TPI simulator for the project will be detailed in the methodology section. As a result, it is expected that GPS simulator will work as a source for TPI and is feasible for LRT Kelana Jaya Line. To conclude, a complete simulation of how the GPS broadcasts its signal which includes coordinates of the train will be done.